(untitled) (Eurasian Journal of Philology Science and Education, 2021)
Purpose of this article includes investigation of metaphor’s function in the literary heritage by E. Zamyatin. The science research involves historical-functional method of analyzing the artistic context from the point of view of its socio-historical component. The using of the comparative-textual method contributes the comparing creativity the works by E. Zamyatin with the Russian classical literary tradition and Western literary works is represented as well. The method of receptive aesthetics made it possible to focus on the actualization and concretization of the artistic context of E. Zamyatin and to identify the author’s strategy and aesthetic priorities of the writer The structure of Zamyatin’s narrative is distinguished by a high degree of metaphorization, and metaphors can reflect the state of mind of a certain character through the prism of his perception of the surrounding reality, and, on the other hand, be that figurative means through which the author expresses his personal position. The metaphoric plot of the artistic narrative of E. Zamyatin is based on metaphors-antitheses, when there is a semantic transition of one metaphor in the text into the semantics of another. The personality and work of E. Zamyatin have become the subject of not only critical articles, but also quite deep research in England and the USA. Western critics called the writer an unsurpassed satirist and stylist. They were distinguished by the intellectuality and unique individualism of the Russian writer. The creative manner of E. Zamyatin was also associated with the term «modernism». Western researchers considered the Russian writer not only an innovator in the field of structure and stylistics of artistic narrative, but also a deep adherent of great humanistic principles.